Changes to Saccade Behaviors in Parkinson’s Disease Following Dancing and Observation of Dancing - Cameron, Ian; Brien, Donald; Links, Kira; Robichaud, Sarah; Ryan, Jennifer; Munoz, Douglas; Chow, Tiffany (Frontiers in Neurology, 2013)
Background: The traditional view of Parkinson’s disease (PD) as a motor disorder only treated by dopaminergic medications is now shifting to include non-pharmacologic interventions. We have noticed that patients with PD obtain an immediate, short-lasting benefit to mobility by the end of a dance class, suggesting some mechanism by which dancing reduces bradykinetic symptoms. We have also found that patients with PD are unimpaired at initiating highly automatic eye movements to visual stimuli (pro-saccades) but are impaired at generating willful eye movements away from visual stimuli (anti-saccades). We hypothesized that the mechanisms by which a dance class improves movement initiation may generalize to the brain networks impacted in PD (frontal lobe and basal ganglia, BG), and thus could be assessed objectively by measuring eye movements, which rely on the same neural circuitry. Methods: Participants with PD performed pro- and anti-saccades before, and after, a dance class. “Before” and “after” saccade performance measurements were compared. These measurements were then contrasted with a control condition (observing a dance class in a video), and with older and younger adult populations, who rested for an hour between measurements. Results: We found an improvement in anti-saccade performance following the observation of dance (but not following dancing), but we found a detriment in pro-saccade performance following dancing. Conclusion: We suggest that observation of dance induced plasticity changes in frontal-BG networks that are important for executive control. Dancing, in contrast, increased voluntary movement signals that benefited mobility, but interfered with the automaticity of efficient pro-saccade execution.